2016
DOI: 10.1080/15592294.2016.1226451
|View full text |Cite
|
Sign up to set email alerts
|

DNA methylation profiling in human lung tissue identifies genes associated with COPD

Abstract: Chronic obstructive pulmonary disease (COPD) is a smoking-related disease characterized by genetic and phenotypic heterogeneity. Although association studies have identified multiple genomic regions with replicated associations to COPD, genetic variation only partially explains the susceptibility to lung disease, and suggests the relevance of epigenetic investigations. We performed genome-wide DNA methylation profiling in homogenized lung tissue samples from 46 control subjects with normal lung function and 11… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
86
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(92 citation statements)
references
References 50 publications
6
86
0
Order By: Relevance
“…Epigenetic alterations are associated with a wide variety of diseases including cancers (reviewed in [224]), imprinting disorders [225], and more recently lung diseases [226,227]. IPF is associated with genome-wide changes in chromatin structure [228][229][230] and DNA methylation [231][232][233][234][235].…”
Section: Chapter III Dna Methylation Of the Muc5b Promoter In Ipf Intmentioning
confidence: 99%
“…Epigenetic alterations are associated with a wide variety of diseases including cancers (reviewed in [224]), imprinting disorders [225], and more recently lung diseases [226,227]. IPF is associated with genome-wide changes in chromatin structure [228][229][230] and DNA methylation [231][232][233][234][235].…”
Section: Chapter III Dna Methylation Of the Muc5b Promoter In Ipf Intmentioning
confidence: 99%
“…In skeletal muscle, it mainly reduces muscle tissue by inhibiting the differentiation of muscle satellite cells and thus increases the incidence of COPD. The study of Morrow et al on DNA methylation in COPD patients showed that the loci of differential methylation were located in CHRM1, GLT1D1 and C10 or f11, and if they were ranked by GWAS P -value, the top loci included FRMD4A, THSD4 and C10 or f11 57. In the process of muscle development, microRNAs (miRNAs) play an important role, and many miRNAs are tissue-specific, and miR-1, miR-133 and miR-206 are abundant in skeletal muscle.…”
Section: Othersmentioning
confidence: 99%
“…The results of previous epigenome-wide association studies (EWASs) of spirometric measures of respiratory function and respiratory disease have produced inconsistent results, with some identifying significant associations, [3][4][5][6] and others not. [7][8][9] Moreover, there has been little consistency between the positive findings reported.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9] Moreover, there has been little consistency between the positive findings reported. 9,10 Studies of lung tissue 5,8 have been constrained by sample availability, with the largest study to date comprising 160 subjects. 5 Inconsistency amongst the results of the peripheral bloodbased studies 3,6,7,9,11 is likely to be due to a number of factors, including small sample size (e.g., two studies had less than 200 samples) 6,11 and/or investigation of a relatively small number (~27,000) of CpG loci.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation